Polyphyly of Mesadenus (Orchidaceae, Spiranthinae) and a New Genus from the Espinhaço Range, Southeastern Brazil - Salazar, Gerardo A. (2019)
Mesadenus displays an odd disjunction, with most species found in the southeastern USA, the Caribbean, and Mexico south to El Salvador, and two outliers occurring in southeastern Brazil. A recent molecular phylogenetic study showed that, as currently delimited, Mesadenus is polyphyletic, and further study of this little-known genus is required. Here we assessed relationships in Mesadenus and to other genera conducting a cladistic parsimony analysis of nucleotide sequences of nuclear (ITS) and plastid (matK-trnK, trnL-trnF) DNA for an enlarged sample of taxa, including five out of six currently accepted species of Mesadenus and representatives of nearly all (36 out of 41) genera of Spiranthinae, plus suitable outgroups. A detailed comparison of vegetative and floral attributes of relevant taxa was also conducted. Our results confirm the polyphyly of Mesadenus and support the creation of a new genus, Espinhassoa, to include Brazilian ‘Mesadenus’ glaziovii and ‘M.’ rhombiglossus (as Espinhassoa glaziovii and E. rhombiglossa, respectively). An identification key, descriptions, and illustrations of the two species herein included in Espinhassoa are provided.